FANATISME PENGGEMAR NADIN AMIZAH (ANALISIS ISI KONTEN PADA AKUN TIKTOK @CNADACC) - Irbah, Ais (Commsphere: Jurnal Ilmu Komunikasi, 2024)
Nadin Amizah is a singer and songwriter who started his career in 2016 and is still active today. Nadin is an active singer who has just released an album entitled